Collaborative attitudes between pharmacists and physicians in Brazil (Brazilian Journal of Pharmaceutical Sciences, 2023)
Pharmacist-physician collaboration is a strategy for optimizing patient care and improving health outcomes. Nevertheless, there is a lack of information in Brazil about collaborative practices among these professionals. The aim of this study was to measure collaborative attitude of pharmacists and physicians who were working together in a teaching hospital. A cross-sectional study was conducted from June 2018 to January 2019 with pharmacists and physicians working in a teaching hospital in Northeastern Brazil. These professionals were invited to provide responses to the Brazilian version of the “Scale of Attitudes Towards Pharmacist-Physician Collaboration” (SATP2C); their scores ranged between 16 and 64 points. The software Epi Info TM (version 3.5.4) was used for data analysis, and data were expressed in means. Forty-four professionals participated in this study. The mean age was 33.5 (DP = 7.1) years. More than half of participants were male (n = 25, 56.8%). The means from the SATP2C for pharmacists and physicians were 54.20 and 50.91, respectively, indicating good collaborative attitudes. There was no statistical difference between the mean scores of pharmacists and physicians. Participants showed a predisposition for collaborative teamwork. Future studies should focus on understanding the process by which collaboration translates into clinical practice.